Relative extent of double and single Auger decay in molecules containing C, N and O atoms. Issue 36 (5th September 2016) - Roos, A. Hult; Eland, J. H. D.; Andersson, J.; Zagorodskikh, S.; Singh, R.; Squibb, R. J.; Feifel, R.
Abstract : We show that the proportion of double Auger decay following creation of single 1s core holes in molecules containing C, N and O atoms is greater than usually assumed, amounting to about 10% of single Auger decay in many cases. Abstract : We show that the proportion of double Auger decay following creation of single 1s core holes in molecules containing C, N and O atoms is greater than usually assumed, amounting to about 10% of single Auger decay in many cases. It varies from molecule to molecule, where the size of the molecule has a positive correlation to the amount of double Auger decay. In neon, examined as a related benchmark, the proportion of double Auger decay is similar to that in methane, and is in the order of 5%.